Early migration of biliary stent leading to free intra-peritoneal duodenal perforation- A Case Report - Butt, Roshan; Butt, Usman Ismat; Khan, Wasim Hayat; Yasin, Fahad; Klasra, Abid; Wadood, Abdul (Journal of the Pakistan Medical Association, 2022)
Intestinal perforation from a plastic biliary stent is a known but rare complication of endoscopic biliary stent placement. Intra-peritoneal perforation is less common but carries more morbidity and mortality. Only a few cases of early stent migration and perforation have been reported. We present the case of a duodenal perforation caused by early migration of plastic biliary stent that resulted in intra-peritoneal biliary peritonitis. Keywords: Biliary stent, bowel perforation, early migration.